Hyperglycemia-associated Alzheimer’s-like symptoms and other behavioral effects attenuated by Plumeria obtusa L. Extract in alloxan-induced diabetic rats - Naz, Sumeera; Imran, Imran; Farooq, Muhammad Asad; Shah, Syed Adil Hussain; Ajmal, Iqra; Zahra, Zartash; Aslam, Aqsa; Sarwar, Muhammad Irfan; Shah, Jaffer; Aleem, Ambreen (Frontiers in Pharmacology, 2022)
Diabetes mellitus is a chronic metabolic complaint with numerous short- and long-term complications that harm a person’s physical and psychological health. Plumeria obtusa L. is a traditional medicine used in the treatment of diabetes to reduce complications related to behavior. Plumeria is a genus with antipsychotic activities. The objective of this study was to examine the effects of a methanolic extract of Plumeria obtusa L. in the attenuation of diabetes, on symptoms of Alzheimer disease, and on other associated behavioral aspects. A single dose of alloxan was administered to an experimental group of rats to induce development of diabetes (150 mg/kg, intraperitoneal) and the rats were then administered selected doses of methanolic extract of Plumeria obtusa L. (Po.Cr) or glibenclamide (0.6 mg/kg) for 45 consecutive days. Behavioral effects were evaluated using three validated assays of anxiety-related behavior: the open field test, the light and dark test, and the elevated plus maze. Anti-depressant effects of Plumeria obtusa L. were evaluated using the forced swim test (FST) and memory and learning were assessed using the Morris water maze (MWM) task. Po.Cr was also evaluated for phytochemicals using total phenolic content (TPC), total flavonoid content (TFC), and high-performance liquid chromatography assays, and antioxidant capability was assessed through assays of DPPH radical scavenging, total oxidation capacity, and total reducing capacity. In the alloxan-induced model of diabetes, the administration of Po.Cr and glibenclamide for 45 days produced a marked decrease (p < 0.001) in hyperglycemia compared to control animals. Po.Cr treatment also resulted in improvement in indicators, such as body weight and lipid profile (p < 0.05), as well as restoration of normal levels of alanine transaminase (ALT) (p < 0.001), a biomarker of liver function. Diabetic rats presented more Alzheimer-like symptoms, with greater impairment of memory and learning, and increased anxiety and depression compared to non-diabetic normal rats, whereas treated diabetic rats showed significant improvements in memory and behavioral outcomes. These results demonstrate that Po.Cr reversed alloxan-induced hyperglycemia and ameliorated Alzheimer-related behavioral changes, which supports additional study and assessment of conventional use of the plant to treat diabetes and associated behavioral complications.